Coping efforts and resilience among adult children who grew up with a parent with young-onset dementia: a qualitative follow-up study. Issue 1 (1st January 2016) - Johannessen, Aud; Engedal, Knut; Thorsen, Kirsten
Abstract : Background: It is estimated that one in four persons with young-onset dementia (YOD) (<65 years old) has children younger than 18 years old at the onset of the dementia. These children experience a childhood different from what is expected. Adult children of parents with YOD are seldom addressed in research, and the impact of the dementia on the children's development over time has rarely been studied. Aim: The goal of this study was to explore how adult children experienced the influence of their parents' dementia on their own development during adolescence; what coping efforts, strategies, and resources they employed; and how they evaluated the most recent changes in their life situation. Method: A follow-up, grounded theory approach in two phases was used. Qualitative interviews with 14 informants (18–30 years of age) were conducted in 2014 and one year later, in 2015. Findings: Nearly all the informants expressed that their emotional well-being and their life situation were better at the second interview compared to the time of dementia onset in their parents. To overcome the difficulties of being a child of a parent with YOD, they used different instrumental, cognitive, and emotional coping strategies, subsumed analytically under the concept detachment . This category covers three subcategories of coping strategies: moving apart, greater personal distance, and calmer emotional reactions . Another category, resilience, designates combinations of the coping strategies. Vital for the development of coping resources and resilience was the need the informants had for social support—for people they saw who listened to them and responded to their needs. Conclusion: Most of the informants reported that they experienced a better life situation and less emotional stress over time as their parent's dementia progressed. They developed better coping capacities and greater resilience. Vital for the development of coping resources and resilience was the need the informants had for social support.